Otoritas Negara Dalam Pengaturan Kehidupan Beragama Di Indonesia : Urgensi Ataukah Intervensi - Muntoha Muntoha (Millah: Journal of Religious Studies, 2012)
This article explores the harmony and freedom of  religious life in Indonesia. A number of issues concerning freedom of religion sprung from religious-based violence, the banning of certain doctrines, to the criminalization of those deemed heretical in religious activity. For that, we need a concrete role in regulating the state of religious life through the harmonization of a number of official policy.